Relationship of arterial tonometry and exercise in patients with chronic heart failure: a systematic review with meta-analysis and trial sequential analysis - Gong, Xiaodan; Hu, Mengwen; Li, Mei (BMC cardiovascular disorders, 2022)
Arterial stiffness is a common characteristic in patients with chronic heart failure (CHF), and arterial tonometric technologies related to arterial stiffness are novel and effective methods and have an important value in the diagnosis and prognosis of CHF. In terms of ameliorating arterial stiffness in patients with CHF, exercise training is considered an adjuvant treatment and also an effective means in the diagnosis and judgment of prognosis. However, there are huge controversies and inconsistencies in these aspects. The objective of this meta-analysis was to systematically test the connection of arterial tonometry and exercise in patients with CHF. Databases, including MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) in The Cochrane Library, were accessed from inception to 7 March 2022. The meta-analysis was then conducted, and trial sequential analysis (TSA) was performed jointly to further verify our tests and reach more convincing conclusions by using RevMan version 5.4 software, STATA version 16.0 software, and TSA version 0.9.5.10 Beta software. Eighteen articles were included, with a total of 876 participants satisfying the inclusion criteria. The pooling revealed that flow-mediated dilation (FMD) was lower in basal condition [standardized mean difference (SMD): - 2.28%, 95% confidence interval (CI) - 3.47 to - 1.08, P < 0.001] and improved significantly after exercise (SMD: 5.96%, 95% CI 2.81 to 9.05, P < 0.001) in patients with heart failure with reduced ejection fraction (HFrEF) compared with healthy participants. The high-intensity training exercise was more beneficial (SMD: 2.88%, 95% CI 1.78 to 3.97, P < 0.001) than the moderate-intensity training exercise to improve FMD in patients with CHF. For augmentation index (AIx), our study indicated no significant differences (SMD: 0.50%, 95% CI - 0.05 to 1.05, P = 0.074) in patients with heart failure with preserved ejection fraction (HFpEF) compared with healthy participants. However, other outcomes of our study were not identified after further verification using TSA, and more high-quality studies are needed to reach definitive conclusions in the future. This review shows that FMD is lower in basal condition and improves significantly after exercise in patients with HFrEF compared with healthy population; high-intensity training exercise is more beneficial than moderate-intensity training exercise to improve FMD in patients with CHF; besides, there are no significant differences in AIx in patients with HFpEF compared with the healthy population. More high-quality studies on this topic are warranted.